USING THE ZOOM APPLICATION TO SUPPORT ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Elpika Yenes; Firman; Riska Ahmad (Literasi Nusantara, 2021)
Due to the spread of COVID-19 in Indonesia, all Indonesian students need to study online from home. Padang State University is one of the institutions that implements e-learning using the Zoom application. Zoom Cloud Meeting is one of the most frequently used e-learning resources at Padang State University. In online learning, it is very important to pay attention to what students understand as learning progresses. The purpose of this study was to find out and understand how to use e-learning with the Padang State University Zoom application in the pedagogy class. The research method used is literature study based on data from various articles, reference books and other complementary documents. Based on the results of the study, it was found that e-learning using the Zoom application was widely applied to the learning process. Online learning is very attractive to students because of its more flexible learning methods. Online learning allows students to be more independent and more active in their learning. Many of Zoom's features make learning even more fun. In addition, students can feel the understanding and acceptance of the lecturer.